EVALUASI KESESUAIAN LAHAN UNTUK PENGEMBANGAN BUDIDAYA UDANG WINDU (Penaeus monodon) SISTEM SILVOFISHERY DI KECAMATAN SERUWAY: Indonesia - Wijaya, Panca Dharma; Iswahyudi; Rosmaiti (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2024)
The existence of a silvofishery system is expected to enhance the productivity of local communities in shrimp farming, specifically for the tiger shrimp. Efforts that need to be made in the development of tiger shrimp farming with a silvofishery system must be well-evaluated for land suitability. Land suitability analysis for pond cultivation needs to be conducted as a basis for decision-making regarding land use that is compatible with its suitability. This research was conducted in the community ponds in Lubuk Damar and Sungai Kuruk III villages, Seruway District, Aceh Tamiang Regency, Aceh Province. The study was carried out over four months, from August to November 2023. This research used a survey method with descriptive techniques based on field observations and laboratory analysis. The approach used in this survey research is an evaluative approach. The method employed in this study is a matching method. Based on the results of the land suitability evaluation at the research locations, it was found that there was an S3 (Marginally Suitable) land suitability class at three sample points, while an N1 (Currently Unsuitable) land suitability class was found at the fourth sample point. The limiting factors identified in this study include climate (precipitation), mangrove density, clay content, and ammonia levels. Improvement efforts to achieve an S1 land suitability class for mangrove density include reforestation or replanting mangroves to maintain the mangrove ecosystem. Additionally, efforts to improve clay content to reach an S1 land suitability class, which is currently too high, can be done by applying lime. High ammonia levels can also be addressed to achieve an S1 land suitability class by controlling water quality and creating water circulation. However, the climatic limiting factors present at the research locations cannot be improved, as they are natural factors.